ENERGY EFFICIENT MULTI SERIES HLV BURNER SYSTEM FOR INFRARED GAS HEATING OF INDUSTRIAL PREMISES - , Н. Н. (Municipal economy of cities (Technical science), 2013)
The paper describes a series of energy-efficient systems multigorelochnyh for HLV Infrared heating gas production facilities, describe their advantages, recommendations for further use.